APLIKASI SISTEM INFORMASI GEOGRAFIS TARI TRADISIONAL SUMATERA UTARA BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract— North Sumatra has a traditional dance art that has been around since tens or even hundreds of years ago and has a high historical value because the dance is characteristic of tribal customs that exist in North Sumatra. Many peoples and tourists did not have much information about traditional dance in North Sumatra that resulted in a lack of tourist interest to visit in North Sumatra in the of history and culture traveler. Traditional dance art GIS application is created to provide information about traditional dance and easier for users in order to know the traditional arts in North Sumatra, with the facilities given to the user that allows the point of knowing the location, a description of the dance existing traditional and also supported by other facilities that are useful for tourist